Effects of Selenium-Enriched Yeast on Performance, Egg Quality, Antioxidant Balance, and Egg Selenium Content in Laying Ducks - Zhang, Xiufen; Tian, Lu; Zhai, Shuangshuang; Lin, Zhenping; Yang, Huiyong; Chen, Junpeng; Ye, Hui; Wang, Wence; Yang, Lin; Zhu, Yongwen (Frontiers in Veterinary Science, 2020)
This study investigated the effects of dietary selenium-enriched yeast (Se yeast) supplementation on the laying performance, egg quality, plasma antioxidant balance, and egg selenium (Se) content in laying Longyan ducks. A total of 480 32-week-old ducks were randomly divided into four dietary treatments, each consisting of six replicates of 20 ducks. The dietary treatments were a control basal diet and basal diets with supplementation of 0.05, 0.15, and 0.25 mg Se/kg via Se yeast. The analyzed Se contents of the four diets were 0.15, 0.21, 0.36, and 0.43 mg Se/kg, respectively. Dietary Se yeast supplementation had no apparent effects on laying performance and egg quality (p > 0.05), but it improved the antioxidant balance of ducks, as inferred by greater glutathione peroxidase and catalase activities, and decreased the malondialdehyde content in plasma of ducks (p < 0.05). It was suggested that the Se content in the basal diet containing 0.15 mg/kg of Se requirement is adequate for productive performance, but not for the antioxidant balance of laying ducks. Besides that, the Se contents in the yolk, albumen, and whole egg increased linearly as the Se supplementation levels increased. With more feeding days, the Se contents in the yolk and whole egg from non-Se-yeast-supplemented ducks increased linearly (p < 0.05), while those from Se-yeast-supplemented ducks showed a quadratic relationship (p < 0.05). In conclusion, the Se content of the basal diet at 0.15 mg/kg was adequate for laying performance and egg quality traits in laying ducks. Dietary Se yeast supplementation is beneficial to improve the antioxidant balance of laying ducks and increase the Se deposition in eggs for producing Se-enriched eggs. Based on the quadratic model or the quadratic broken-line model analyses, supplemental 0.19 mg Se/kg via Se yeast, with a total equivalent of 0.34 mg Se/kg in the diet, could provide the optimum antioxidant balance in laying ducks. Dietary supplementation of 0.25 mg Se/kg via Se yeast, with a total equivalent of 0.40 mg Se/kg in the diet, could lead to achieving the desired Se content in the whole egg.